Alternatives to Settlement of Conflicts in Islamic Banking An Analytical Study - Husni, Ahmad Muhammad; Husni, Amin Muhammad (IOSR Journal Of Humanities And Social Science (IOSR-JHSS), 2019)
The emergence and spread of Islamic banks in most parts of the world and its international and daily dealings with the international financial institutions created disputes and conflicts between Islamic banks that are governed by the Shari’ah in all their dealings, and between traditional institutions that are governed by the regulations and laws that are contrary to Islamic law. Thus, there is a need for a way of settling these disputes, such as litigation, suit, and the consequence of that requires the presence of the litigant parties, and advocacy at the judiciary, and the requirement of evidence and witness and litigation cost etc. The question is what is the possibility of implementing the judicial ruling and compelling the party at fault of implementing the ruling? The aim of this study is to explain the Shari’ah ruling in issues relating to financial conflicts and how to resolve the dispute between them and strengthen the role of Islamic jurisprudence in the lives of contemporary people and its ability to deal with emerging issues and to create Shari’ahcriterion or alternative ways of settlement of disputes between them. The study adopted the descriptive and analytical method by referring to ancient and modern sources to find out Shari’ah matters relating to the study, and to express the views of ancient and contemporary scholars with authorities and their strength and to select the best view in the conflicting issues. The study found some results, among which are: There must be differentiation between International law and international arbitrators who rely on the rule that are based on justice and equality between the States and the laws that are based on the beliefs and rules contrary to Islamic law.